Sistem Informasi Akuntansi Pada PT. Pradnyana Artha Mandiri - Sugiartawan, Putu; Suprihanto, Didit (INFOTEKS (Information Technology, Computer and Sciences), 2020)
The financial management business process of PT. Pradnyana Artha Mandiri records are carried out by using bookkeeping, which can result in damage and loss of these data, the recapitulation of report preparation will take a long time because you have to double-check all transactions that occur and are prone to errors and manipulations that will affect company revenues because it does not have a good data monitoring system. Based on the above background, the formulation of the problem in the research is How to Design and Build a financial information system in a company, while the research objective to be achieved in the reporting process is to be able to design and build a company financial information system. The benefits that can be obtained from the results of this study are expected to assist in the processing of transactions, making it easier in making financial reports, and the results of this study are expected to be useful and can be used as input for companies to improve employee performance. As for the writing of this research, the problem is limited so as not to deviate from the problems that have been formulated. These limitations include this system does not discuss employee payroll, the system created discusses the calculation of transaction data which includes incoming transactions, outgoing transactions, general journal reports, big reports as well as the company's income statement.